La Ética de la Investigación en las Ciencias Humanas o Sociales - Soto*, Jairo Soto (Amauta, 2014)
RESUMEN Las personas que poseen conducta asertiva tienen entre sus principales señas de identidad el que siempre cumplen sus promesas, que reconocen defectos y virtudes, se sienten bien consigo mismos y hacen sentir bien a los demás, respetan al resto y siempre acaban consiguiendo sus metas. A partir del siglo XVIII, la libertad comenzó a unirse a otras facultades o virtudes, como la justicia y la igualdad. Entonces se observa que las decisiones propias afectan a las de los demás y la ética nos enseña a la elección de una conducta digna. El hombre tiene una doble condición: es un ser biológico, pero también un ser cultural y social. La dignidad está relacionada a la excelencia, la gravedad y el decoro de las personas en su manera de proceder. Un sujeto que se comporta con dignidad es alguien de elevada moral, sentido ético y acciones honrosas. Las personas indignas actúan guiadas por el instinto que es de naturaleza biológica. La ética profesional pretende regular las actividades que se realizan en el marco de una profesión. Podría decirse, que la ética profesional estudia las normas vinculantes recogidas por la deontología profesional. Habermas intenta ofrecer una fundamentación racional de la ética, también de una ética negativa. La propuesta de Habermas sería una “criba” (criba-crítica, krínein). Es también una ética universalista. Palabras clave Conducta humana, Libertad, Dignidad, Ética comunicativa. ABSTRACT Assertive behavior is the kind of behavior we want. People who have it are among its main identity which always keep their promises, recognizing both their flaws and their virtues, they feel good about themselves and feel also well for others. They respect the other and always end up getting their goals. From the eighteenth century, freedom began to join other faculties or virtues, such as justice and equality. Thereafter it is observed that scheduling decisions affect others rights and ethics teaches us the choice of decent behavior. This allows men how to organize their freedoms and their moral boundaries. Men have two conditions He is a biological, but also a social and cultural being and this condition gives their human dignity. Dignity is related to excellence, gravity and decorum of the people in the way they behave. A man who behaves with dignity is someone of high moral, ethical and honorable actions. People act unworthy guided by instinct that it is from biological nature. We suggest the need to build a homus Ethicus, from education in this way, each of us, by our actions, will be seeking a more sustainable and just world, promoting the common welfare rather than the particular benefit. Professional ethics seeks to regulate the activities carried out within the framework of a profession. Arguably, therefore, that professional ethics rules binding studies collected by professional ethics. Habermas who is intended to provide a rational foundation of ethics. Habermas’s proposal would be a “screen” (screen-critical krinein). It is also a universal ethic. Through the principle of universality can aspire to the validity of those rules that get or can get the approval of all participants of all practical discourse. Keywords Human behavior, Freedom, Dignity, Ethics communicative.